Macroeconomic stability or cyles? The role of the wage-price spiral - Dag Kolsrud; Ragnar Nymoen (University of Oslo, Department of Economics, 2010)
We derive aggregate supply (AS) relationships for an intermediate-run macro model. The wage-price spiral provides the conceptual framework for a synthesis of different contesting theoretical and empirical perspectives on the AS curve: the Phillips curve model (PCM) and the wage-price equilibrium correction model (WPECM). The generalized AS curve is grafted into a small macro model. We analyze stability conditions, steady states, and dynamic solutions, using a combination of algebra and mulations. The specification of the AS curve, as a PCM or a WPECM, is shown to be important for all aspects of the model's solution, but within each model also the detailed parameterization is of qualitative importance. For example, endogenous cyclical fluctuations are typical for both nominal and real variables, e.g. inflation and unemployment.
Keywords: E24; E30; J50; 330; AS-AD; Cyles; dynamics; equilibrium correction; macroeconomics; nominal rigidity; Phillips curve; unemployment; wage-price spiral; Gesamtwirtschaftliches Angebot; Preis-Lohn-Spirale; Preisrigidität; Lohnrigidität; Phillips-Kurve; Dynamisches Modell; Multivariate Analyse; Makroökonomik